НОВОЕ В ГЕОЛОГИИ И ГЕОХИМИИ УГЛЕЙ АНАБАРСКОГО РАЙОНА ВОСТОЧНОЙ СИБИРИ - Толстов А.В. (My University, 2000)
The coal occurrences at the Anabar area are formed thick layers. The coal deposits from the Aptian rocks occurred in the favorable geological and mine-technical conditions for the profitable extraction. The explored coal resources make possible the commercial mining these deposits some hundred years.
Keywords: 552.574;553.94:622.2;622.1.031(571.56-16)